INFLUENCE OF THE USE OF GEOTHERMAL WATER TO THE MALT DRYING SYSTEM FOR THE CONTROL OF DRYING CHARACTERISTICS USING AI-BASED CONTROL SYSTEMS - Iancu Carmen Violeta; Borza Ioana Maria; Lazăr Andra Nicoleta; Gitea Manuel Alexandru; Mureșan Roxana Maria; Bei Mariana Florica (Natural Resources and Sustainable Development)
In the current perspective of sustainable development, non-conventional energies represent a challenge for research in the field. Geothermal energy can be considered a sustainable energy source, it being easy to implement in the countries where it is found as a natural resource, being a viable alternative to fossil fuels and is supported for its technical-economic and environmental advantages. Romania is one of the lucky countries from this point of view. The purpose of this work is to study the control of the malt drying system, through the influence of geothermal water on the drying characteristics. The numerical model of the malt drying system with geothermal water was developed using both the P.I.D. controller. as well as the Fuzzy controller in order to determine the control of the drying characteristics (temperature and thermal flow at the exit from the dryer) to obtain the humidity of the malt within the admissible limits, and the temperature inside the dryer not to alter the grain of malt.